Students care about stunting in children: Universitas Pendidikan Indonesia community service program in Karawang Village Cianjur Regency - Meizia Ziharani; Salsa Nissa Agustin (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2024)
Indonesia still faces nutritional problems, which seriously impact the quality of human resources (HR). One of the problems of malnutrition that is still relatively high in Indonesia includes the issue of stunting and emaciation in toddlers, as well as the problem of anemia and chronic energy deficiency (CED) in pregnant women. The theme "The Important: Caring for Stunting" invites UPI KKN students to play their role as agents of change to overcome the problem of stunting in society. Students are expected to be able to get closer to communities affected by stunting, learn about the root causes, and develop concrete solutions that can be implemented on a local scale. This KKN activity was carried out on 26 July - 26 August 2023. Located in Karangwangi village, Ciranjang District, Cianjur Regency. The work program procedures for this activity were carried out in collaboration with the TP-PKK regarding posyandu services, stunting outreach to PAUD, and PHBS outreach to Karangsari Elementary School. From the results of this work program, it is hoped that we will know more about stunting and can prevent stunting in children in the future. The hope is that the stunting rate in Indonesia can decrease, especially in Karangwangi Village itself; the stunting rate is at 0 (zero), so this hope can be maintained.   Abstrak Indonesia masih menghadapi permasalahan gizi yang berdampak serius terhadap kualitas sumber daya manusia (SDM). Salah satu permasalahan gizi buruk yang masih cukup tinggi di Indonesia antara lain masalah stunting dan kekurusan pada balita serta masalah anemia dan kekurangan energi kronik (KEK) pada ibu hamil. Tema “Si Penting: Peduli Stunting” mengajak mahasiswa KKN UPI untuk menjalankan peran sebagai agen perubahan dalam upaya mengatasi masalah stunting di masyarakat. Mahasiswa diharapkan dapat mendekatkan diri dengan masyarakat yang terkena dampak stunting, belajar tentang akar penyebabnya, serta mengembangkan solusi konkret yang dapat diterapkan dalam skala lokal. Kegiatan KKN ini dilaksanakan pada tanggal 26 Juli - 26 Agustus 2023. Bertempat di desa Karangwangi, Kecamatan Ciranjang, Kabupaten Cianjur. Prosedur program kerja kegiatan ini dilaksanakan dengan kerjasama dengan pihak TP-PKK mengenai pelayanan posyandu, sosialisasi stunting ke PAUD, dan sosialisasi PHBS ke pihak SD Karangsari. Dari hasil program kerja tersebut diharapkan dapat lebih tahu tentang stunting dan bisa mencegah terjadinya stunting pada anak ke depannya. Harapannya adalah agar angka stunting di Indonesia dapat menurun, terlebih di Desa Karangwangi sendiri angka stunting berada di angka 0 (zero), sehingga harapan tersebut dapat dipertahankan. Kata Kunci: Kuliah kerja nyata; PHBS; sosialisasi stunting; stunting